SOME THEORETICAL ASPECTS OF MODERN CLASSIFICATION OF FINANCIAL SANCTION - Ustynova, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article analyzing existing views on the institution of financial responsibility, including clustering analysis and classification of financial sanctions correct existing classifications is necessary for legislators and business financial relationships.